Corbynism in perspective : the Labour Party under Jeremy Corbyn - Roe-Crines, Andrew (Building progressive alternatives., 2021)
This carefully researched collection of essays assesses the influence and legacy on the Labour Party of one of its most popular and yet divisive leaders.